2012
DOI: 10.1007/s00418-012-0998-0
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the E-cadherin repressors Snail, Slug and Zeb1 in urothelial carcinoma of the urinary bladder: relation to stromal fibroblast activation and invasive behaviour of carcinoma cells

Abstract: Epithelial-mesenchymal transition (EMT) is regulated by interaction of carcinoma and stromal cells and crucial for progression of urinary bladder carcinoma (UBC). Therefore, the influence of activated fibroblasts on the expression of E-cadherin repressors as well as EMT and invasion in UBC was investigated. A correlative analysis of the immunohistochemical expression of fibroblast (ASMA, S100A4, FAP, SDF1, PDGFRβ) and EMT (Snail, Slug, Zeb1, E-cadherin) markers was performed on 49 UBC cases of different stages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
42
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(51 citation statements)
references
References 51 publications
5
42
1
2
Order By: Relevance
“…EMT is widely associated with lymphatic metastasis of several malignant tumors. 7,13,22,23 However, in this series we found no such association. A low sample size effect could explain this phenomenon.…”
Section: Discussioncontrasting
confidence: 71%
“…EMT is widely associated with lymphatic metastasis of several malignant tumors. 7,13,22,23 However, in this series we found no such association. A low sample size effect could explain this phenomenon.…”
Section: Discussioncontrasting
confidence: 71%
“…However, the knowledge of the precise mechanisms in their relationship is very limited. It is well known that the loss of E-cadherin is the fundamental event in EMT and that this loss is induced by several E-cadherin repressors such as Snail, Slug and ZEB1 [28]. Here, we found that the protein expression levels of ZEB1, Snail, and SLUG were increased in the TMZ-resistant cells compared with the glioblastoma cells, indicating that EMT might contribute to the TMZ resistance of the glioblastoma cell line.…”
Section: Discussionsupporting
confidence: 60%
“…Furthermore, when cells lose apico-basal polarity, this goes hand in hand with a loss of adherens junctions and vice versa. Accordingly, EMT is often driven by repressing the expression of adherens junction components, such as E-cadherin; owing to the pivotal role of E-cadherin loss, transcription factors that affect EMT, such as Snail, Twist and Zebs, are often referred to as E-cadherin repressors (Galván et al, 2015;Nieto, 2011;Schulte et al, 2012). Intriguingly, it is also possible to affect EMT via the repression of apico-basal polarity proteins without affecting E-cadherin transcription; the loss of apico-basal polarity in turn leads to destabilisation of adhesion junctions (Campbell et al, 2011;Lim and Thiery, 2011).…”
Section: Adherens Junctions Cell Adhesion and Apico-basal Polaritymentioning
confidence: 99%